2018
DOI: 10.2147/vhrm.s163228
|View full text |Cite
|
Sign up to set email alerts
|

Low nitric oxide level is implicated in sickle cell disease and its complications in Ghana

Abstract: BackgroundNitric oxide (NO) plays a fundamental role in maintaining normal vasomotor tone. Recent clinical and experimental data suggest that NO may play a role in the pathogenesis and therapy of sickle cell disease (SCD). The aim of this study was to determine NO metabolites (NOx) in SCD patients at steady state and in vaso-occlusive crisis (VOC), as well as those with hemolytic clinical sub-phenotype that includes leg ulcers and priapism.MethodologyThis was a case–control cross-sectional study conducted on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Elevated PLT counts recorded could be attributed to the outcome of the interaction between the sickled cells and the endothelial cells as a result of the vasoocclusion during microcirculation [8]. Generally, patients with HbS are known to have a significantly higher mean total WBC count [28] and findings from this study were not an exemption. Out of the 113 participants whose hematological parameters were retrieved, majority of both males and females with HbSS were severely anemic, as reported by Jadhav [29].…”
Section: Discussionmentioning
confidence: 64%
“…Elevated PLT counts recorded could be attributed to the outcome of the interaction between the sickled cells and the endothelial cells as a result of the vasoocclusion during microcirculation [8]. Generally, patients with HbS are known to have a significantly higher mean total WBC count [28] and findings from this study were not an exemption. Out of the 113 participants whose hematological parameters were retrieved, majority of both males and females with HbSS were severely anemic, as reported by Jadhav [29].…”
Section: Discussionmentioning
confidence: 64%
“…Findings from the study also suggest in part that the lower levels of SOD and CAT in patients with the SS genotype may be due to significant depletion of antioxidants, such as nitric oxide and vitamins, in these patients. Lower levels of vitamin E [ 39 , 40 ] and nitric oxide [ 41 ] were reported in sickle cell patients with the SS genotype in previous studies. The non-significant differences in levels of SOD and CAT between some of the study participants is partly due to, perhaps, a similar ongoing haemolysis and associated conditions in the patients.…”
Section: Discussionmentioning
confidence: 97%
“…Several other studies have reported that levels of VCAM-1 are particularly increased in severe complications of SCD, including HbSS vaso-occlusive crises [7,8,9] and acute chest syndrome [10], and thus, may serve as a promising biomarker of disease severity and associated complications of SCD [9]. Although levels of NO as well as its metabolites and soluble adhesion molecules have been exploited in single cohort studies among SCD patients [7,8,9,17,25], a correlation between the two has not been given a closer look. In another study, a significant correlation was observed between nitrate and endothelial adhesion molecules in patients with systemic sclerosis [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical manifestations of SCD, levels of NO metabolites are particularly reduced during a vaso-occlusive crisis [15,16,17]. NO is involved in the suppression of adhesion molecule expression on endothelial cells [18].…”
Section: Introductionmentioning
confidence: 99%